Affective Temperament Profiles in Patients with Multiple Sclerosis: Association with Mood Disorders - ÖZKAN, Adile (Noro Psikiyatr Ars, 2016)
INTRODUCTION: The aim of the present study was to screen for bipolarity and to investigate the affective temperaments of patients with multiple sclerosis (MS) and the possible association between the clinical and demographic characteristics of MS patients and temperament profiles. METHODS: A total of 65 patients with MS and 66 healthy volunteers completed the 32-item hypomania checklist (HCl-32), the Mood Disorder Questionnaire (MDQ), and the Temperament Evaluation of Memphis, Pisa, Paris, and San Diego-Autoquestionnaire (TEMPS-A) tests. The HCl-32, MDQ, and TEMPS-A scores were compared between the patients and healthy volunteers. RESULTS: MS patients had significantly higher scores for the depressive, cyclothymic, irritable, and anxious domains of the TEMPS-A scale than the control group, whereas relapsing remitting MS (RRMS) patients had higher MDQ and TEMPS-A hyperthymia scores than secondary progressive MS patients. MS patients who were being treated with interferon beta 1-b therapy had significantly higher MDQ scores than those being treated with interferon beta 1-a, glatiramer acetate, or who were without medication. Expanded Disability Status Scale (EDSS) scores were positively correlated with TEMPS-A depressive and hyperthymic temperaments. CONCLUSION: Our results suggest that higher scores for affective temperament in MS patients indicate subclinical manifestations of mood disorders. Higher hyperthymia scores and manic symptoms detected in the RRMS group could shed light on the relationship between bipolarity and MS. Thus, the screening of bipolarity and affective temperament profiles in MS patients could help clinicians predict future mood episodes and decrease their impact on disease severity.